Alih dan Campur Kode dalam Vlog Youtube Iday Adventurer: Analisis Wacana Digital - Fadli, Muhammad Faisal (Departement of Arabic Language and Literature, 2026)
Video-based social media platforms such as YouTube function not only as entertainment media but also as digital discourse spaces where linguistic practices are constructed, performed, and publicly negotiated. This study aims to analyze code-switching and code-mixing practices in the YouTube vlog Iday Adventurer and to explain their discursive functions in cross-cultural communication within digital environments. Employing a qualitative approach with a case study design, the data consist of selected utterances from vlog videos involving interactions between the main speakers, local communities in Saudi Arabia, and online audiences. Data analysis is conducted using the Computer-Mediated Discourse Analysis (CMDA) framework, which emphasizes the relationship between language choice, digital media context, and audience orientation. The findings reveal that code-switching and code-mixing function as discursive strategies for audience management, digital persona construction, and the negotiation of social and cultural differences in multimodal and performative online communication. Theoretically, this study contributes to the development of digital sociolinguistics by conceptualizing bilingualism as a discursive practice rather than a purely structural linguistic phenomenon. Practically, the findings provide insights for content creators, language educators, and digital communication practitioners in designing effective, adaptive, and context-sensitive language strategies for multilingual social media contexts.